The Greek nouns in the Coptic papyrus P.KRU 74 (Circe de clásicos y modernos, 2025)
The aim of our study is to analyze the nominal loanwords of Greek origin in the Coptic text of P.KRU 74, based on an examination of the corresponding Greek nouns and the semantic and historical context of these words. To this end, we have divided our study into two parts. In the first part, we identify the equivalent Greek nouns in the Coptic text of P.KRU 74. In the second part, we examine the meaning of each noun from a semantic and historical perspective, a study that, in some cases, can extend from the classical or Ptolemaic period to the 8th century AD. Finally, we include an Appendix with the Coptic text and our translation.